Cystatin B increases autophagic flux by sustaining proteolytic activity of cathepsin B and fuels glycolysis in pancreatic cancer: CSTB orchestrates autophagy and glycolysis in PDAC. Issue 12 (10th December 2022) - Jiang, Yongsheng; Han, Lijie; Xue, Meilin; Wang, Ting; Zhu, Youwei; Xiong, Cheng; Shi, Minmin; Li, Hongzhe; Hai, Wangxi; Huo, Yanmiao; Shen, Baiyong; Jiang, Lingxi; et al.
Abstract: Background: Both autophagy and glycolysis are essential for pancreatic ductal adenocarcinoma (PDAC) survival due to desmoplasia. We investigated whether targeting a hub gene which participates in both processes could be an efficient strategy for PDAC treatment. Methods: The expression pattern of glycolysis signatures (GS) and autophagy signatures (AS) and their correlation with cystatin B (CSTB) in PDAC were analysed. It was discovered how CSTB affected the growth, glycolysis, and autophagy of PDAC cells. We assessed competitive binding to cathepsin B (CTSB) between CSTB and cystatin C (CSTC) via immunoprecipitation (IP) and immunofluorescence (IF). Chromatin immunoprecipitation quantitative polymerase chain reaction (ChIP‐qPCR) and luciferase reporter gene assays were used to unveil the mechanism underlying CSTB upregulation. The expression pattern of CSTB was examined in clinical samples and KrasG12D/+, Trp53R172H/+, Pdx1‐Cre (KPC) mice. Results: GS and AS were enriched and closely associated in PDAC tissues. CSTB increased autophagic flux and provided substrates for glycolysis. CSTB knockdown attenuated the proliferation of PDAC cells and patient‐derived xenografts. The liquid chromatography‐tandem mass spectrometry assay indicated CSTB interacted with CTSB and contributed to the proteolytic activity of CTSB in lysosomes. IF and IP assays demonstrated that CSTB competed with CSTC to bind to CTSB. Mutation of the key sites of CSTB abolished the interaction between CSTB and CTSB. CSTB was highly expressed in PDAC due to H3K27acetylation and SP1 expression. High expression of CSTB in PDAC was observed in tissue microarray and patients' serum samples. Conclusions: Our work demonstrated the tumorigenic roles of autophagy and glycolysis in PDAC. CSTB is a key role in orchestrating these processes to ensure energy supply of PDAC cells. Abstract : Both glycolysis and autophagy processes were obviously active in pancreatic ductal adenocarcinoma (PDAC). Cystatin B (CSTB) promotes autophagic flux by competing with cystatin C to bind to cathepsin B and provides substrates for glycolysis in PDAC. High H3K27ac levels in the promoter region and SP1 upregulation contributed to the high expression of CSTB.